STRATEGI KOMUNIKASI POLITIK DPC PDI PERJUANGAN SURABAYA PADA PEMILU LEGISLATIF 2019 - Abdul Hakim; Redi Panuju (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Dewan Pengurus Cabang (DPC) Partai Demokrasi Indonesia Perjuangan (PDIP) Surabaya is a local political partywhich succeeded in preserving its victory in the 2019 Legislative Election with the acquisition of 15 seats. This study aims to determine the political communication strategies used by the Indonesian Democratic Party of Struggle (PDIP) during the 2019 elections. This study uses a qualitative approach with employing in-depth interview and observationmethods. The data obtained were analyzed through an interactive analysis model including data reduction, data display, and drawing conclusions. This research founds the PDI Perjuangan political communication model is more based on the transactional model. This communication model illustrates the ongoing communication process between the sender of the message (party and candidates) and the recipient of the message (community). Of course, during the campaign there were obstacles or disturbances, one of which was money politics. As a consequence, the community should elects their candidates and parties during the 2019 Elections.DPC Partai Demokrasi Indonesia (PDI) Perjuangan Kota Surabaya merupakan politik lokal yang berhasil mempertahankan kemenangan di Pemilu Legislatif 2019 dengan perolehan 15 kursi. Penelitian ini bertujuan untuk mengetahui stategi komunikasi politik yang dipakai PDI Perjuangan selama Pemilu 2019. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi dan wawancara mendalam. Data yang diperoleh dianalisis dengan model analisis interaktif meliputi reduksi data, sajian data, dan penarikan simpulan. Temuan penelitian ini adalah model komunikasi politik PDI Perjuangan lebih pada model transaksional. Model komunikasi ini menggambarkan proses komunikasi yang berlangsung secara berkesinambungan antara pengirim pesan (partai dan caleg) serta penerima pesan (masyarakat). Kendala uatam selama kampanye yaitu politik uang, sebagai umpan balik (feedback), masyarakat memilih caleg dan partai tersebut saat Pemilu 2019.